Antimicrobial Resistance Pattern of Bacterial Isolates from Intensive Care Unit of a Tertiary Care Hospital in Bangladesh (Bangladesh Journal of Medical Microbiology, 2017)
Infections with resistant strain are one of the leading causes of morbidity and mortality in hospitalized patients especially the critically ill patients in intensive care unit (ICU). The present study was conducted to know the changing pattern of antibiotic resistance of the common isolates from blood, urine, respiratory secretions and pus/ wound swab of patients admitted in ICU at Holy Family Red Crescent Medical College hospital over a two years period from January 2012 to December 2013. A total of 1282 samples were analyzed. Out of which 301 (23.5%) samples were positive for growth of organisms. The predominant isolates were E.coli (28%), Klebsiella (27%), Acinetobacter (17.3%), Pseudomonas (9.6%), Staphylococcus aureus (5.3%) & candida (6%). Majority isolates were resistant to Cephalosporin and Amoxycillin, (>70-90%). Carbapenem were still highly active against E.coli. However, Klebsiella, Pseudomonas and Acinetobacter were showing alarming resistance (55-60%) towards those drugs. Aminoglycosides resistance has also increased for Pseudomonas and Klebsiella. The percentage of Cloxacillin resistant for staphylococcus was near about 40%. The most active drug against Pseudomonas was piperacillin/Tazobactam. The positive result from this study was that organisms showed decreased resistance towards Tetracycline, Cotrimoxazole and Ciprofloxacin. The sensitivity of Nitrofurantoin for urinary isolates was good. Regular surveillance of antibiotic susceptibility pattern & judicious use of antibiotics is very important for reducing the infection rate and antimicrobial resistance.Bangladesh J Med Microbiol 2014; 08 (01): 07-11